2016
DOI: 10.1515/hukin-2015-0193
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement abnormalities in essential tremor

Abstract: Essential tremor (ET) is the most prevalent movement disorder, characterized mainly by an action tremor of the arms. Only a few studies published as yet have assessed oculomotor abnormalities in ET and their results are unequivocal. The aim of this study was to assess the oculomotor abnormalities in ET patients compared with the control group and to find the relationship between oculomotor abnormalities and clinical features of ET patients. We studied 50 ET patients and 42 matched by age and gender healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
2
9
0
1
Order By: Relevance
“…Of additional interest is that these oculomotor abnormalities were particularly evident among those ET patients who also exhibited intention tremor [76], which as noted above canonically has been viewed as a sign of cerebellar dysfunction. The presence of sub-clinical eye movement abnormalities in ET patients has been confirmed in several additional studies [77,78]. Second, several studies have revealed abnormalities in limb motor behavior in ET [79][80][81][82][83].…”
Section: Clinicalmentioning
confidence: 73%
“…Of additional interest is that these oculomotor abnormalities were particularly evident among those ET patients who also exhibited intention tremor [76], which as noted above canonically has been viewed as a sign of cerebellar dysfunction. The presence of sub-clinical eye movement abnormalities in ET patients has been confirmed in several additional studies [77,78]. Second, several studies have revealed abnormalities in limb motor behavior in ET [79][80][81][82][83].…”
Section: Clinicalmentioning
confidence: 73%
“…A case-control study of 50 patients with essential tremor reported that the latency of reflexive saccades was associated with severity of tremor. Additionally, an increased incidence of dysmetria was seen during reflexive saccades in patients with more severe disease 57…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Estudos que avaliaram o rastreamento ocular indicaram a possibilidade de existência de 1 início sacádico (Helmchen et al, 2003;Wójcik-Pędziwiatr et al, 2016). Observou-se também que a espessura foveal medida pela Tomografia de Coerência Óptica (OCT) pode ser um biomarcador promissor para TE e DdP (Satue et al, 2016;Sharifi et al, 2014).…”
Section: Resultsunclassified